Abelmoschus esculentus facial mask / Muhammad Aidil Ikhwan Kamarudin, Mohamad Syamil Mohd Nor and Mohammad Hafis Ayob - Kamarudin, Muhammad Aidil Ikhwan; Mohd Nor, Mohamad Syamil; Ayob, Mohammad Hafis (Faculty of Plantation and Agrotechnology, 2023)
Abelmoschus esculentus pod contains polyphenolic compounds, carotene, folic acid, thiamine, riboflavin, niacin, vitamin C, oxalic acid, and amino acids. Abelmoschus esculentus seed contain polyphenolic compounds, mainly oligomeric catechins and flavanols derivatives, protein (i.e., high lysine levels), and oil fraction (in particular, its derived oil is rich in palmitic, oleic, and linoleic acids). This study aimed to formulate a sheet mask of Lady Finger extract, and examined its moisturizing effect on volunteers' skin. This was the new innovation, which build the new beauty treatment product using Abelmoschus esculentus. Abelmoschus esculentus was combined with the cold powder using the method that was stated by the author. There have many benefits of Abelmoschus esculentus in the beauty treatment product as stated by the author in the journal below. Abelmoschus esculentus are suitable to be the main ingredient due to the benefit that has been stated by the author in the journal.